Anlisis fundamental dan prediksi earning pada perusahaan manufaktur di Bursa Efek Jakarta (BEJ) - Mas'ud Machfoedz (Jurnal Akuntansi dan Auditing Indonesia, 1999)
This paper examines the association between fundamental signals used by Lev and Thiagarajan (1993) and future earnings using 52 sample of manufacturing firm listed in the Jakarta Stock Exchange (JSX). Results of the study indicate the from the aggregate score of the nine fundamental signals, there of the signals were significantly associated with the change in one-year-ahead earnings per share (EPS), but not with mean change in two-year ahead EPS. This study also founds that the change in one-year-ahead EPS was also associated with the year(s) as control variable(s).